(untitled) (Open Academia: Journal of Scholarly Research, 2025)
Tashkent is recognized by the world community as a peaceful, friendly, hospitable, bread city. And it also has the status of "Gate of the East" “Capital of Islamic Culture”. Today, in the period when Tashkent is turning into one of the major metropolises in the region and the world, the current topic is the study and study of its culture, history in the Middle Ages. In medieval sources, the city of Tashkent was called Shash. It was from here that a large number of scholars emerged, whose activities were closely connected with such Islamic sciences as fiqh, hadith studies, etc. Scholars who were born and made a great contribution to Islamic teaching with their scientific activities were given the title (nisba) of "Shashi", and later (from the 16th century) "Tashkandi". It was by this name that they became famous throughout the Muslim world